STRATEGI PEMBELAJARAN JARAK JAUH PADA MATERI SIMULASI DIGITAL: MASALAH, SOLUSI, HAMBATAN, PRAKTIK EFEKTIF - Shofwan ‘Arif (ADISAM PUBLISHER, 2024)
The COVID-19 pandemic has had a significant impact on various sectors of life, particularly in the field of education. To uphold social distancing, schools were closed, and face-to-face learning was suspended until the situation stabilized. Online learning, which was implemented during the pandemic, continues to be utilized even after the pandemic has ended, including in vocational education such as digital simulation materials. Learners study from home, presenting challenges for teachers in preparing the lessons. Eflective learning strategies are crucial for success in online education. The aim of this article is to elucidate eflective strategies for online learning. This scholarly article employs a literature study method as its data source, involving processes of identification, evaluation, and synthesis with several journals as references and supported by books to strengthen the researcher’s arguments. From the results of the literature review, it was found that: 1) There are obstacles in online learning, with many individuals unprepared for it and facing difficulties in achieving learning objectives. 2) Eflective online learning strategies can be defined as anything systematically designed by teachers to address all aspects of online learning. 3) Strategies that teachers can implement to conduct online learning eflectively include: mastering the use of online media, providing alternative access methods, enhancing interaction and participation of students, and oflering support and guidance.